2010
DOI: 10.1055/s-0029-1245813
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium Score: Influence of the Reconstruction Interval on Cardiac Risk Stratification in Asymptomatic Patients using Dual-Source Computed Tomography

Abstract: Despite the increased temporal resolution of DSCT examinations, the Agatston and volumetric scores depend on the reconstruction time within the cardiac cycle. The fact that the greatest relative variability for both the Agatston score and the volumetric score was found in young patients with small amounts of coronary calcium may result in different treatment strategies for young patients depending on the reconstruction used. Therefore, more accurate risk stratification may require the analysis of multiple reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The same holds true about CACS and hence, nowadays MSCT is much more widely used than EBCT for CACS (23). A high image quality is obtained using MSCT scanners when utilizing retrospective ECG-gating technique to find the most appropriate phase with least motion artifact (24, 25). Moreover, Horiguchi et al have shown that using prospective ECG-triggered scan at 45% of R-R interval in a 64-slice MSCT scanner provides a constantly high image quality irrespective of heart rate, body mass index or background noise level (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same holds true about CACS and hence, nowadays MSCT is much more widely used than EBCT for CACS (23). A high image quality is obtained using MSCT scanners when utilizing retrospective ECG-gating technique to find the most appropriate phase with least motion artifact (24, 25). Moreover, Horiguchi et al have shown that using prospective ECG-triggered scan at 45% of R-R interval in a 64-slice MSCT scanner provides a constantly high image quality irrespective of heart rate, body mass index or background noise level (26).…”
Section: Resultsmentioning
confidence: 99%
“…Not only the slice thickness is of paramount importance, but also the reconstruction interval of slices has its impact on CACS. The effect of using varying reconstruction intervals in 16-slice MSCT scanner is assessed by Schlosser et al (34); while recently, it has been demonstrated to have a significant importance in CACS accuracy using dual-source CT scanners, particularly in cases of low calcium score (24). Frequent use of CACS protocol as a routine adjunct of CCTA leads to increase of patient’s radiation dose.…”
Section: Resultsmentioning
confidence: 99%
“…AS, as well as volume score (VS), was significantly dependent on the reconstruction interval. During CACS using an updated version of MDCT, dual-source CT, a significant influence of image reconstruction interval on accuracy of CACS was observed, particularly in cases with low CACS [20]. They suggested that accurate and reproducible quantification of coronary calcium appeared to require analysis of multiple reconstructions.…”
Section: Coronary Artery Calcium Scoring Techniquesmentioning
confidence: 99%
“…In contrast, EBCT showed superiority to MDCT by lower radiation dose and shorter acquisition time [26]. However, the current version of MDCT reaches low radiation dose and high temporal resolution during CACS scanning [20,33]. According to a recent report by Horiguchi et al [34], CACS at prospective ECG-triggered 64-slice MDCT showed constant high image quality at 45% R-R acquisition without influence of heart rate, body-mass-index, or level of background noise.…”
Section: Imaging Modalities For Cacsmentioning
confidence: 99%
“…10 % aller publizierten Beiträge. Wie es sich für ein in der klinischen Routine verankertes Gebiet gehört, finden sich neben rein methodischen Beiträgen immer mehr Arbeiten, deren Ziel die Beurteilung der prognostischen Bedeutung der gewonnenen Erkenntnis aus der Herz-CT oder Herz-MRT ist [110,111]. Das gilt gleichermaßen für elektive Untersuchungen wie für den Einsatz in der Notfalldiagnostik [112,113].…”
unclassified